Efektivitas Posteromedial Release yang Dikombinasikan dengan Subtalar Release pada Congenital Talipes Equinovarus: Suatu Tinjauan Sistematis: The Effectiveness of Posteromedial Release by Subtalar Release for Congenital Talipes Equinus Varus (CTEV): A Systematic Review - Sandy, I Putu Lari; Maharjana, Made Agus (Chakra Brahmanda Lentera Institute, 2026)
Clubfoot, or congenital talipes equinovarus (CTEV), strikes about 1–2 in 1,000 newborns, featuring forefoot adduction, hindfoot varus, equinus, and cavus deformities that, if untreated, cause lasting disability. While the Ponseti method remains the gold standard, tough resistant cases call for surgery like posteromedial release (PMR) or complete subtalar release (CSTR) yet no clear winner emerges for long-term results or recurrence rates. This study compares their outcomes using recent evidence. This PRISMA-guided systematic review compared PMR and CSTR for CTEV treatment, analyzing peer-reviewed clinical studies from 2005–2025 on recurrence, complications, functional outcomes, and operative parameters; four studies met inclusion criteria. The search across PubMed, Google Scholar, and ScienceDirect used Boolean operators—(“CTEV” OR “Congenital talipes equinus varus”) AND (“Posteromedial release” OR “modified posteromedial release”) AND (“Complete subtalar release” OR “modified complete subtalar release”) including full-text English clinical reports/series on resistant clubfoot while excluding reviews, abstracts, non-English/out-of-timeframe works, duplicates, animal studies, and similar materials. PROSPERO (Registration ID: CRD420251159365). The four studies (short- and long-term follow-up) showed both PMR and CSTR effectively correct CTEV, with no significant differences in clinical outcomes, recurrence rates, radiological improvements, or functional results. Patient age, postoperative care, and rehabilitation influenced long-term outcomes. Complications included CSTR overcorrection and PMR scar issues, emphasizing careful surgical planning. This review suggests that both PMR and CSTR are effective treatments for resistant clubfoot, with no clear advantage of one over the other. Future studies should focus on larger sample sizes, standardized outcome measures, and longer follow-up to determine the most effective surgical approach for CTEV.